Economía circular en residuos de aparatos eléctricos y electrónicos. - Oblitas, J. (2019)
Currently, the use of natural resources, the challenge of laws and environmental sustainability, as well as waste management, receive considerable attention. The research aims to analyze the circular economy as a strategy in the management of waste electrical and electronic equipment, through a descriptive, nonexperimental study, considering the discarded laptops in a university. The study was carried out in two stages: The first, a proposal for a remanufactured product where the potential of laptop parts to be recycled based on 110 recycled equipment was examined; the second, a business strategy based on the circular economy, in order to identify the perception of the offer of remanufactured computers, for this purpose a tool validated by experts was designed, which was applied to 367 university students. As a result, the relationship between the socioeconomic level and the acceptance of remanufactured personal computers was determined, finding significant correlations. It is concluded that the studied circular economy is an adequate alternative for the management of computer parts waste, in addition a positive perception of this type of products was observed according to the computing needs of the users.